Pengembangan Sistem Manajemen Informasi Laboratorium Komputer Berbasis Standar Nasional Indonesia/International Standard Organisation 17025:2017 - Pradana, Egi Adithia; Abdillah, Fatimah (Indo-MathEdu Intellectuals Journal, 2024)
Learning is a system that cannot be separated from other components that interact with each other within it. Based on this, learning or education can be supported or accompanied by various components, one of which is computer technology. SNI/ISO 17025 is a standard from ISO which regulates organization, calibration and binding rules related to laboratories. This research uses the extreme programming research method because this method is most suitable for research and development of computer labs which are constantly developing both technologically and policy, Referring to the problems above, there is a need for research that can help solve problems and reduce the bureaucratic chain, time wasted if you want to report damage and/or borrow equipment or tools to laboratory assistants, it is necessary to develop a computer laboratory management system, referring to SNI /ISO 17025 as a laboratory management standard is expected for computer laboratory management to be more organized, disciplined and accountable. Good laboratory management and in accordance with SNI/ISO 17025 standards will result in better governance compared to disorganized laboratories, because it is superior in terms of order, security and so on, thus minimizing losses such as loss of equipment, undetected damage. and others.